Antidumping and safeguard measures in the political economy of liberalization : the Mexican case - de la Torre, Luz Elena Reyes (Policy research working paper, 2005)
"Mexico's creation and use of safeguard and antidumping processes to advance its liberalization illustrate three key points: (1) The country was able to use the instruments without losing political control. In a period of crisis that threatened congressional approval of critical steps in the liberalization-brought on by currency overvaluation and recession, along with unexpected demands from the United States in the North American Free Trade Agreement negotiations-the government applied a number of trade defense measures. Once the problems were addressed with adequate instruments the number of measures dropped drastically. The instruments had not been captured by protection-seeking interests; (2) The country adopted a liberalization-accepting measure of international norms. An important innovation that Mexico made operational was the use within World Trade Organization (WTO) rules of prevailing international prices as the measure of competition that industry was expected to meet. The WTO rules would also have allowed the use of other standards-as in traditional antidumping-using countries-that impose less discipline. Moreover, the Mexican standard was consistent with the government-industry understanding that though Mexican industry would be protected against extraordinary circumstances it would be expected to face up to international competition; (3) Political judgment and political courage are essential. While mastery of the technical elements of a safeguard or antidumping investigation is mandatory, sustaining liberalization depends in significant part on the political skills to know when to emphasize the technical elements, when to rely more on the discretion the government retains under the rules, and on the courage to do it. "--World Bank web site